GeoChip as a metagenomics tool to analyze the microbial gene diversity along an elevation gradient - Gao, Ying (Genom Data, 2014)
To examine microbial responses to climate change, we used a microarray-based metagenomics tool named GeoChip 4.0 to profile soil microbial functional genes along four sites/elevations of a Tibetan mountainous grassland. We found that microbial communities differed among four elevations. Soil pH, temperature, NH(4)(+)–N and vegetation diversity were four major attributes affecting soil microbial communities. Here we describe in details the experiment design, the data normalization process, soil and vegetation analyses associated with the study published on ISME Journal in 2014 [1], whose raw data have been uploaded to Gene Expression Omnibus (accession number GSM1185243).